2014
DOI: 10.1186/1471-2334-14-541
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a novel avian influenza A (H7N9) virus in humans by multiplex one-step real-time RT-PCR assay

Abstract: BackgroundA novel avian influenza A (H7N9) virus emerged in eastern China in February 2013. 413 confirmed human cases, including 157 deaths, have been recorded as of July 31, 2014.MethodsClinical specimens, including throat swabs, sputum or tracheal aspirates, etc., were obtained from patients exhibiting influenza-like illness (ILIs), especially from those having pneumonia and a history of occupational exposure to poultry and wild birds. RNA was extracted from these samples and a multiplex one-step real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…To verify the positive results amplified by the multiplex assay, 12 positive samples with the H3N2 virus, 8 positive samples with the pandemic (H1N1) 2009 virus and 5 positive samples with the reassortant avian H7N9 virus were randomly selected to analyse their HA genomic sequences that were confirmed by the Sangon Biotech Co., Ltd (Shanghai, China). These results strongly indicated that the multiplex rRT-PCR assay in the study was completely in accordance with the assay systems previously described (Chen et al 2011; Kang et al 2014; World Health Organization 2013; Fan et al 2014; Nie et al 2013; Kuo et al 2014). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To verify the positive results amplified by the multiplex assay, 12 positive samples with the H3N2 virus, 8 positive samples with the pandemic (H1N1) 2009 virus and 5 positive samples with the reassortant avian H7N9 virus were randomly selected to analyse their HA genomic sequences that were confirmed by the Sangon Biotech Co., Ltd (Shanghai, China). These results strongly indicated that the multiplex rRT-PCR assay in the study was completely in accordance with the assay systems previously described (Chen et al 2011; Kang et al 2014; World Health Organization 2013; Fan et al 2014; Nie et al 2013; Kuo et al 2014). …”
Section: Discussionsupporting
confidence: 85%
“…Sixteen H subtypes (H1–H16) and nine N subtypes (N1–N9) have been found in avian species, while the H17N10 and H18N11 subtypes have emerged in bats (Bedford et al 2015; Wu et al 2014; Fan et al 2014). Human infections with FluA viruses are commonly associated with the human H1, H2, and H3 subtypes that can cause outbreaks of FluA virus infection, such as the seasonal H3N2 virus and the pandemic (H1N1) 2009 virus (Cox and Subbarao 2000; Chen et al 2011; Bedford et al 2015; Davlin et al 2016; Yang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A method was developed for the detection of avian influenza A/ H7N9 using real-time PCR with a detection limit of 3.2 Â 10 À4 and 6.4 Â 10 À4 haemagglutination units (HAUs) for the H7 and N9 genes, respectively [27,28]. A microfluidics chip (fabricated using polydimethylsiloxane) with real-time fluorescence detection for the rapid identification of AIV H5 was suggested by Zhu et al [29].…”
Section: Conventional Methods: Elisa and Pcrmentioning
confidence: 99%
“…Internal standard primers and probes based on the sequences of Homo sapiens ribonuclease P were designed to monitor specimen extraction, RT-PCR amplification, and microarray hybridization. This marker has been described as a reliable internal positive control marker in several publications (Dare et al 2016; Fan et al 2014). All the primers and probes were confirmed using BLAST program of NCBI and then synthesized using Sangon Biotech Co., Ltd. (Shanghai).…”
Section: Methodsmentioning
confidence: 99%